2021
DOI: 10.32811/25954482-2021v4n2p115
|View full text |Cite
|
Sign up to set email alerts
|

Violência causada aos profissionais de saúde durante a pandemia da COVID-19

Abstract: Nesse estudo objetivou-se ampliar o debate sobre a violência no trabalho de profissionais de saúde durante a pandemia da doença COVID-19, por meio de um estudo narrativo e reflexivo com foco na temática da violência laboral entre os profissionais de saúde atuantes durante a pandemia da COVID-19; foi desenvolvido em junho de 2020 e foi pautado em noticiários internacionais e nacionais e publicações sobre a temática. Verificou-se um eixo condutor que foi denominado Debate sobre a violência no trabalho de profiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Deficiencies in physical structures and material resources, a lack of suitable places to rest and eat, disorganization, and unsuitable working environments were situations experienced by these workers, which—over and beyond exposure to COVID-19—constituted situations of institutional violence to which nurses were exposed. Even though these conditions were not perceived explicitly by the study participants, they can be identified in declarations regarding unfavorable work environments in the interviews [ 13 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in physical structures and material resources, a lack of suitable places to rest and eat, disorganization, and unsuitable working environments were situations experienced by these workers, which—over and beyond exposure to COVID-19—constituted situations of institutional violence to which nurses were exposed. Even though these conditions were not perceived explicitly by the study participants, they can be identified in declarations regarding unfavorable work environments in the interviews [ 13 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Durante la pandemia de COVID-19, se observó en Brasil una falsa romantización del trabajo de enfermería, visto como sacerdocio o heroísmo, que no se reflejó en cambios reales en las condiciones de trabajo. Como ejemplo más brutal, los profesionales de enfermería fueron objeto de violencia en el trabajo, ya sea por defender medidas de protección y cuidado científicamente legitimadas, o por ser vistos como una fuente de contaminación (30)(31) .…”
Section: Discussionunclassified
“…During the COVID-19 pandemic, a false romanticization of nursing work was observed in Brazil, seen as priesthood or heroism, which was not reflected in real changes in working conditions. As a more brutal example, nursing professionals were subject to violence at work, whether by defending scientifically legitimized protection and assistance measures, or by being seen as a source of contamination (30)(31) .…”
Section: Discussionmentioning
confidence: 99%